Desain Baru Logo Halal Badan Penyelenggara Jaminan Produk Halal: Antara Urgensi, Seni, dan Esensi - Rachman, Abdul; Maemunah, Maemunah; Ulpah, Mariya (el Buhuth: Borneo Journal of Islamic Studies, 2022)
This study aims to analyze the urgency, art, and essence of the new halal logo design issued by the Halal Product Assurance Agency (BPJPH) after the enactment of Law Number 33 of 2014 and Government Regulation Number 39 of 2021 concerning the transfer of authority for administering halal certification from LPPOM of Indonesian Council of Ulama to the Halal Product Guarantee Agency (BPJPH). BPJPH's Halal Logo Design reaps the pros and cons of the Muslim community in Indonesia, both in terms of Arabic writing, the shape of the halal logo that resembles a puppet, and the urgency of a total change from the halal logo of the Indonesian Council of Ulama. This research is interesting to study because the halal logo design is a sign of halal certification of a product and is a halal guarantee for Muslim consumers in Indonesia. This study uses a descriptive qualitative method with a normative juridical approach because it discusses regulations related to guaranteeing halal products in Indonesia both in terms of urgency, art, and essence. This study describes that the total change of the halal logo is not urgent to improve the quality of halal product assurance services in Indonesia. BPJPH's halal logo design puts more emphasis on art than Halal writing in Arabic as a sign that the product is "Halal" so it is difficult to read as a "Halal" sign. The essence of the halal logo is as a sign that the product has been certified halal by BPJPH so that the certainty of halal writing is more considered. Keywords: logo, halal, BPJPH, urgency